Testimonio y ficción en la narrativa argentina - García, Victoria (2018)
The relation between testimony and fiction represented, for Latin American writers who defended testimonial literature in the 60-70s, a dilemmatic option, between clearly defined and mutually exclusive terms.  However, reconsidered today, the link between testimony and fiction shows to be more complex, thus it can be addressed by literary theory. In such sense, this paper studies the relations between testimony and fiction displayed within a series of Argentine post-dictatorship texts. We argue that the articulation of testimony and fiction in such narratives cannot be merely explained as a rhetorical phenomenon. On the contrary, it derives from the complex characteristics of the social experience of State terrorism, which is represented in these texts. Based on a wide corpus which covers from Souvenir of the death by Miguel Bonasso (1984) to Tucho by Rafael Bielsa (2014), we analyze some socio-historical basis of the integration of testimony and fiction in Argentine post-dictatorship narrative.